The budget-minimizing bureaucrat? Empirical evidence from the senior executive service - Dolan, Julie (2002)
In a representative democracy, we assume the populace exerts some control over the actions and outputs of government officials, ensuring they comport with public preferences. However, the growth of the fourth branch of government has created a paradox: Unelected bureaucrats now have the power to affect government decisions (Meier 1993; Rourke 1984; Aberbach, Putnam, and Rockman 1981). In this article, I rely on two competing theories of bureaucratic behaviour-representative-bureaucracy theory and Niskanen's budget-maximization theory-to assess how well the top ranks of the federal government represent the demands of the assess whether Senior Executive Services (SES) members mirror the attitudes of the populace or are likely to inflate budgets for their own personal gain. Contrary to the popular portrayal of the budget-maximizing bureaucrat (Niskanen 1971), I find these federal administrators prefer less spending than the public on most broad spending categories, even on issues that fall within their own departments' jurisdictions. As such, it may be time to revise our theories about bureaucraatic self-interest and spending priorities. - Reproduced.
Keywords: Civil service